Cover Feature: Sustainable Valorisation and Efficient Downstream Processing of Giant Reed by High‐Pressure Carbon Dioxide Pretreatment (ChemPlusChem 10/2022). Issue 10 (23rd August 2022) - Di Fidio, Nicola; Tozzi, Federico; Martinelli, Marco; Licursi, Domenico; Fulignati, Sara; Antonetti, Claudia; Raspolli Galletti, Anna Maria
Abstract : The cover feature image represents the role of carbon dioxide in the proposed biorefinery scheme based on CO2 capture by lignocellulosic biomass and the use of supercritical CO2 for the efficient pretreatment of giant reed under sustainable reaction conditions. The synergistic combination of supercritical CO2, FeCl3 and surfactant PEG400 allowed to selectively produce second‐generation sugars such as glucose, xylose or xylo‐oligosaccharides, which represent value‐added platform chemicals. More information can be found in the Research Article by N. Di Fidio, A. M. Raspolli Galletti, and co‐workers .